Legitimate expectations in civil proceedings: traditional legal understanding and synergetic approach - O. H. Bortnik (Law and Safety)
The subject of the study is legitimate expectations as an object of judicial protection in civil proceedings, as well as the principle of law, due to the hope of a person for a procedure in which the state will ensure effective protection of the violated right or legitimate hope for the state promise. Understanding of these categories directly depends on the method of interpretation and priority of certain forms of law as substantive and formal characteristics that express the law.